Dihydromyricetin supplementation improves ethanol-induced lipid accumulation and inflammation - Janilkarn-Urena, Isis; Idrissova, Alina; Zhang, Mindy; VanDreal, Masha; Sanghavi, Neysa; Skinner, Samantha G.; Cheng, Sydney; Zhang, Zeyu; Watanabe, Junji; Asatryan, Liana; Cadenas, Enrique; Davies, Daryl L. (Frontiers in Nutrition, 2023)
Introduction Excessive alcohol consumption leads to a myriad of detrimental health effects, including alcohol-associated liver disease (ALD). Unfortunately, no available treatments exist to combat the progression of ALD beyond corticosteroid administration and/or liver transplants. Dihydromyricetin (DHM) is a bioactive polyphenol and flavonoid that has traditionally been used in Chinese herbal medicine for its robust antioxidant and anti-inflammatory properties. It is derived from many plants, including Hovenia dulcis and is found as the active ingredient in a variety of popular hangover remedies. Investigations utilizing DHM have demonstrated its ability to alleviate ethanol-induced disruptions in mitochondrial and lipid metabolism, while demonstrating hepatoprotective activity. Methods Female c57BL/6J mice (n=12/group) were treated using the Lieber DeCarli forced-drinking and ethanol (EtOH) containing liquid diet, for 5 weeks. Mice were randomly divided into three groups: 1) No-EtOH, 2) EtOH [5% (v/v)], and 3) EtOH [5% (v/v)] + DHM (6mg/mL). Mice were exposed to ethanol for 2 weeks to ensure the development of ALD pathology prior to receiving dihydromyricetin supplementation. Statistical analysis included one-way ANOVA along with Bonferroni multiple comparison tests, where p ≤ 0.05 was considered statistically significant. Results DHM administration significantly improved aminotransferase levels (AST/ALT) and reduced levels of circulating lipids including LDL/VLDL, total cholesterol (free cholesterol), and triglycerides. DHM demonstrated enhanced lipid clearance by way of increased lipophagy activity, shown as the increased interaction and colocalization of p62/SQSTM-1, LC3B, and PLIN-1 proteins. DHM-fed mice had increased hepatocyte-to-hepatocyte lipid droplet (LD) heterogeneity, suggesting increased neutralization and sequestration of free lipids into LDs. DHM administration significantly reduced prominent pro-inflammatory cytokines commonly associated with ALD pathology such as TNF-ɑ, IL-6, and IL-17. Discussion DHM is commercially available as a dietary supplement. The results of this proof-of-concept study demonstrate its potential utility and functionality as a cost-effective and safe candidate to combat inflammation and the progression of ALD pathology.